IMPLEMENTASI PENGELOLAAN ASET DAERAH PADA DAERAH PEMEKARAN - Dja'wa, Asrianti (Jurnal Multidisipliner Bharasumba, 2023)
This study aims to determine the application of the Minister of Home Affairs Regulation No. 19 of 2016 concerning the management of the regional asset in the regions resulting from the expansion of new regions, a case study in Konawe Kepualaun Regency. Konawe Kepulauan Regency is a Regency resulting from the expansion of the Konawe Regency in 2013. The research method used was a descriptive qualitative analysis method. Data collection was carried out through literature and field studies through indepth interview, with regional asset managers. The results showed that the application of the Minister of Domestic Affairs Regulation on Regional Asset Management was not yet effective and efficient. Starting from the planning needs, procurement, use, utilization, destruction, management, assessment, security and maintenance, elimination, administration, and controls. The cause of ineffective and inefficient asset management in the Konawe Kepulauan Regency lies in the implementation of physical asset inventory, as well as in juridical practices. In the end, it will impact the implementation of legal audits, asset valuation, and optimizing the use of assets that are not optimal, and weak supervision and control.